Magnetic main sequence stars as progenitors of blue supergiants. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Petermann, I.; Castro, N.; Langer, N.
Abstract: Blue supergiants (BSGs) to the right the main sequence band in the HR diagram can not be reproduced by standard stellar evolution calculations. We investigate whether a reduced convective core mass due to strong internal magnetic fields during the main sequence might be able to recover this population of stars. We perform calculations with a reduced mass of the hydrogen burning convective core of stars in the mass range 3–30 M ⊙ in a parametric way, which indeed lead to BSGs. It is expected that these BSGs would still show large scale magnetic fields in the order of 10 G.